Diagnóstico de necessidades de capacitação de servidores públicos federais : uma proposta instrumental com mapeamento de processos - Rochesso, Nátila (2016)
People management is an area that needs attention within a public institution, since the activities developed in it affect the functional life of all the servers of the institution. In addition, it is an area very audited by the Office of the Comptroller General (CGU), which has been finding more and more errors in the execution of activities. Therefore, this research sought to diagnose the training needs of the employees who work in the people management area of a Federal Institute of Education (IFE) through the analysis of the CGU audit reports and the mapping of processes classified as critical. The errors of execution of activities were classified by subjects and, those most critical, had their processes mapped to identify in which step a error happens so that it would be possible to indicate which servers involved in the process need to be trained and in what specifically. The methodological framework considered the qualitative and quantitative study with the use of documentary research and the aid of statistical tools for data analysis and treatment. The sample was based on the audit reports for the years 2009 to 2013, focusing on the area of people management. The results revealed that the critical processes in which the people management servers of the IFE surveyed act are related to the advantage deriving from judicial decision, pension, retirement and reimbursement to the treasury. Finally, this research could be useful for managers in assisting them in their decision-making related to training investments and, with the proposal of mapping critical processes, the points that need to be improved could be better visualized